2019
DOI: 10.1111/fcsr.12327
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of a Father's Role during a Couple's First Pregnancy

Abstract: The objective of this study was to explore the first‐time pregnant couples’ perception of the father's role in relation to a pregnant woman's food and activity behavior during pregnancy. Eleven first‐time pregnant, cohabitating couples across the United States completed a one‐on‐one semi‐structured phone interview for the study. Couples shared similar expectations of a father's role during pregnancy. Fathers were also important in setting and achieving health behavior goals of the pregnant mother. Family and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Examples of some elusive titles include "Reimagining society through retail practice" in JOR, "'Harm or good? ': Consumer perceptions of corporate strategic giving in schools" in JCA, and "Perceptions of a father's role during a couple's first pregnancy" (Greenhill & Vollmer, 2019) in FCSRJ. However, even with those caveats, several…”
Section: Resulting Articles After Exclusionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of some elusive titles include "Reimagining society through retail practice" in JOR, "'Harm or good? ': Consumer perceptions of corporate strategic giving in schools" in JCA, and "Perceptions of a father's role during a couple's first pregnancy" (Greenhill & Vollmer, 2019) in FCSRJ. However, even with those caveats, several…”
Section: Resulting Articles After Exclusionsmentioning
confidence: 99%
“…During the article search, the authors were challenged by many of the resulting titles not being descriptive enough to identify whether it would be included as either a foods/nutrition or fashion/textiles/clothing article; therefore, the extended search to the abstract or article itself was necessary. Examples of some elusive titles include “Reimagining society through retail practice” (Hietanen et al, 2016) in JOR , “‘Harm or good?’: Consumer perceptions of corporate strategic giving in schools” (Aitken & Watkins, 2017) in JCA , and “Perceptions of a father's role during a couple's first pregnancy” (Greenhill & Vollmer, 2019) in FCSRJ . However, even with those caveats, several themes reflective of the FCS Body of Knowledge (Nickols et al, 2009) and possible research foci emerge among all three journals, such as sustainability, career opportunities, the retail environment, physical and social health, consumer decision‐making, demographic diversity, education, technology, financial management, supply chains, and management and personnel.…”
Section: Resultsmentioning
confidence: 99%
“…16 Several authors highlight that a multiple measure is more appropriate because this allows measurement of different aspects of MI, taking into account both emotional and instrumental support. 17 18 Furthermore, qualitative research has shown that the core elements of MI are very similar worldwide, whereby emotional, practical and physical support are key aspects of MI, [19][20][21] making it likely that a global measure would be useful and feasible. On the other hand, studies also show that MI is a context-specific concept, influenced by social and cultural norms, as well as health system factors and policies.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Thus, husbands are required to contribute more to the issues of pregnancy and maternal health (6). In a qualitative study, the couples expressed that the role of fathers was to support mothers emotionally and physically (7). Another qualitative research demonstrated that the more the pregnant women felt attached to their fetus, the more confident and the less worried they were about it (8).…”
Section: Introductionmentioning
confidence: 99%